Water politics in Pakistan: the internal and external dynamics - Lad, M. R.; Jaybhaye, R. G. (IWA Publishing, 2025)
Pakistan, mostly an arid and semi-arid geographic area, paradoxically harbours significant surface and groundwater resources vital for its sustenance. The nation heavily relies on the intricate network of the Indus River system, one of the largest contiguous irrigation networks globally. Despite this, Pakistan faces mounting pressure on its water resources. Hence, this paper delves into the multifaceted factors influencing Pakistan's water availability, categorizing them into internal and external determinants. The internal factors pertain to elements within the nation's borders, while the external factors transcend its sovereign control. The research underscores the imperative for Pakistan to prioritize addressing internal factors that predominantly impact its water resources. Moreover, a growing realization suggests the need for Pakistan to steer away from securitizing water resources. Such an approach complicates fostering amicable relations with its upper riparian neighbours, crucial for collectively addressing challenges such as climate change. Striving for co-operation rather than confrontation is pivotal for navigating these shared challenges sustainably. Finally, the paper concludes that adopting a desecuritized approach towards water resources, coupled with a nuanced focus on internal factors, presents a promising strategy for mitigating water-related concerns in Pakistan.